Academic Supervision of Madrasah Heads in Improving the Teacher’s Performance of Madrasah Tsanawiyah Negeri 2 Tangerang City - Samsudin; Rahman, Abdul; Wasliman, Iim; Sauri, R. Supyan (International Journal of Science and Society, 2024)
This research aims to understand and analyse the academic supervision of Madrasah principals in improving teacher performance at Madrasah Tsanawaiyah Negeri 2 Tangeran City. The research method used was descriptive method with a qualitative approach. Data collection techniques include observation, interviews and documentation. The data analysis technique includes four components, namely, data collection, data reduction, data presentation and drawing conclusions. The research results show that the academic supervision of the madrasa head in improving teacher performance at Madrasah Tsanawaiyah Negeri 2 Tangerang City includes checking the syllabus, annual program, semester program and lesson plans made by the teacher periodically. The supervision model used is a clinical supervision model with a collaborative approach and the techniques used include individual and group techniques. Scheduled supervision is carried out at the beginning and end of each semester, while informally it is carried out every day in guidance or coaching. The obstacles faced in the implementation of academic supervision of madrasa heads at Madrasah Tsanawaiyah Negeri 2 Tangerang City, the main obstacle is time. Factors that influence supervision include internal factors such as intellectual ability and personality, teaching motivation, concern of the madrasah principal, discipline and the presence of teachers.